TRADE IN HIGHER VALUE ADDED AGRI-FOOD PRODUCTS BETWEEN UKRAINE AND THE EUROPEAN UNION - KOZAK, Olga; HRYSCHENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes bilateral trade in agri-food products between Ukraine and the European Union (EU) after the implementation of the Deep and Comprehensive Free Trade Area (DCFTA). It distinguishes between raw and non-raw products involved in foreign trade. The dynamics of exports and imports, the commodity structure, and the impact of the war on trade relations between Ukraine and the EU are analyzed in detail. The article highlights the EU’s growing role as Ukraine’s main partner for agricultural exports. The share of raw materials in the structure of export of agro-food products from Ukraine to different parts of the world is considered. If for the countries of Africa and Asia raw materials export from Ukraine is directly related to food security, the market of the European Union, although it is large, has limited opportunities to absorb Ukrainian raw materials. Oversaturation of the EU domestic market with agri-food products from Ukraine has led to protests by farmers in several EU countries in early 2024. This situation creates additional challenges for Ukraine, emphasizing the need to diversify exports to products with higher added value, in particular oil, poultry meat, fruit and other food products, which are in stable demand among European consumers. It has been proven that the import of agri-food products from the EU to Ukraine remains mainly focused on goods with a higher added value. Continued integration into the EU and Ukraine’s membership prospects stimulate the adaptation of Ukrainian enterprises to European quality standards and technical requirements. Overall, the article underscores the EU’s strategic importance as the main trading partner for Ukrainian agri-food products and the potential of this partnership to support Ukraine’s economic stability.